2012
DOI: 10.1200/jco.2011.40.3568
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Major Postoperative Complications on Health-Related Quality of Life Among Long-Term Survivors of Esophageal Cancer Surgery

Abstract: The occurrence of postoperative complications exerts a long-lasting negative effect on HRQL in patients who survive 5 years after esophagectomy for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
158
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(161 citation statements)
references
References 41 publications
2
158
0
1
Order By: Relevance
“…96,105,106 Early postoperative complications, however, have profound negative effects both in the short and long term. 107 A recent population-based cohort study found that several HRQOL measures are strongly negatively affected up until 10 years after surgery, e.g. reflux, dysphagia and eating difficulties (Figure 4).…”
Section: Survivorshipmentioning
confidence: 97%
“…96,105,106 Early postoperative complications, however, have profound negative effects both in the short and long term. 107 A recent population-based cohort study found that several HRQOL measures are strongly negatively affected up until 10 years after surgery, e.g. reflux, dysphagia and eating difficulties (Figure 4).…”
Section: Survivorshipmentioning
confidence: 97%
“…Along with clinical care, psychosocial intervention amongst cancer patients is very essential to combat the shock and despair after initial diagnosis. It has been indicated that the patient's QOL after surgery not only depends on remaining symptoms or the severity of the disease after surgery, but on the patients' ability to take control and handle the new life situation [19][20][21] . Furthermore, most of the earlier studies have used data from a homogenous sample of patients with stringent exclusion criteria [15,18,23] .…”
Section: Discussionmentioning
confidence: 99%
“…Esophagectomy is the mainstay of treatment for curative intent of local and locally-advanced esophageal cancer (3)(4)(5). Multimodality therapy including esophagectomy is the standard of care in locally-advanced cancer (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, the procedure itself is complex and morbid with up to 10% postoperative mortality (6). Furthermore, the evidence suggests that up to 50% of patients will experience postoperative complications within the first month of surgery (3)(4)(5). Recurrences can occur within the first year following surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation